Assistance Assistance in revitalizing the Water Park KTH Wana Tirta in Bunder Village, Gunungkidul Regency towards a child-friendly tourist park - Nur Rofiq; Kuswan Hadji; Rr. Yunita Puspandari; Tri Agus Gunawan; Satrio Ageng Rihardi (Community Empowerment, 2022)
Gunungkidul Regency is one of several regions in Indonesia that is actively developing the tourism sector in order to support the regional economic sector. At the Water Park KTH Wana Tirta, Bunder Village, Kapanewon Petuk, Gunungkidul Regency, this community service is carried out in the form of counseling and simulation using lecture, discussion, and practice methods. This program resulted in the design of a revitalized child-friendly water park in order to increase the attraction of tourists to the area. In addition, the service team identifies the benefits and drawbacks of water parks, so that it can be used as feedback for better governance and to improve the economy of the surrounding community.